Non-Invasive Salivary Diagnostic Approach for Predicting Dental Caries: Non-Invasive Salivary Diagnosis for Dental Caries - Nisa, Waqar Un; Khan, Muhammad; Haider, Ambreen Khurshid; Imtiaz, Ayesha; Anis, Aisha; Tariq, Fizza; Mushtaque, Saher (Pakistan Journal of Health Sciences, 2024)
Dental caries, often known as tooth decay, is a widespread public health concern that presents many difficulties, especially in developing nations like Pakistan. Objectives: To evaluate a non-invasive salivary diagnostic approach for predicting the risk of dental caries. Methods: In the comparative cross-sectional study, a total of 90 participants were recruited through purposive sampling technique belonging to the age group between 20 and 30 years, which was conducted in one of the private hospitals of Karachi, Pakistan. The participants were placed into two groups for the study according to their oral health state, as determined by the Decayed, Missing, and Filled Teeth index. Both informed consent and ethical approval were acquired. Samples of saliva were collected and examined utilizing standardized tools. Data were analyzed by statistical software version 23.0 by using the Chi-square test. Results: Participants with active caries (Decayed, Missing, and Filled Teeth >5) and those in optimum dental health (Decayed, Missing, and Filled Teeth=0) showed significant differences. Lower salivary pH (p=0.003), decreased flow rate (p=0.001), decreased buffering capacity (p=0.002), and increased viscosity in the high-risk group are important findings. These differences imply altered salivary dynamics, which raise the risk of dental cavities. Conclusions: It was concluded that a non-invasive and efficient method for determining the risk of dental cavities is salivary diagnostics, especially for communities with limited access to preventative dental treatment. Salivary evaluations incorporated into standard dental procedures may improve preventative measures.